## Comparison of the Mathematics Einstein Vs Rohedi

September 5, 2008 by rohedi

Solusi Persamaan diferensial Stochastic

Albert Einstein is the greatest scientist in this century. Because of the greatness, he lifted by his follower as prophet of siences. So didn’t suprise if action of other scientist looked into justify his theory. Masya Allah, this is really abundant. Why? Ya, because in towards the prestisius throne of real sicence, Einstein is not only walks besides do small running („sai“ in term arabic), but he beforehand rides a delman Phytagoras and then takes a rides binomial bus. This statement not without a reason, because in mathematics context, the problem of special relativity only to be form of exploitation from Phytagoras theorem. Greatness of Einstein which is praiseworthy is his excess in exploiting the binomial approach of which is not thinking of other scientist. The fact, his special relativity only applied to movement of object which its speed (v) closing the velocity of light ().

For Detail Visit :

- New Science Future (http://rohedi.blogspot.com)
- ROHEDI Laboratory (http://rohedi.com)

### Like this:

Like Loading...

*Related*

Posted in Science, Stable Modulation Technique | Tagged AF(A) formula, arctangent, Bernoulli, binomial, Differential Equation, duffing oscillator, Einstein, Floquent, maradona, nonlinear differential equation, numerical method, perturbation, Phytagoras, Pocker-Planck, Ricatti, rohedi, Runge-Kutha, stable modulation technique, stochastic resonances | 6 Comments

on September 15, 2008 at 8:47 am |AntoniEinstein geverns his theory using simple mathematics not in differential equation. But why do you attempt to compare Einstein’s mathematics with yours?

on September 15, 2008 at 8:56 pm |rohediOkey Mr.Antoni, we are waiting another comments. Thank’s.

on September 16, 2008 at 10:04 pm |Mr. AF(A)Dear, All

I read on the internet how to solve the following Bernoulli DE (differential equation) :

y’ + y = xy3

which it solution is as follow :

let w = y(1-n) = y1-3 = y-2

dw/dy = -2y-3

(y’ + y = xy3 ) * dw/dy

w ‘ + yw’ = -2x

w’ + (y*-2y-3 ) = -2x

w’ + ( -2y-2 ) = -2x

Remeber that y-2 = w

w’ – 2w = -2x

solve using integrating factor: – h(x) = e∫ -2 dx = e-2x

-h(x) = e2x

w(x) = -h(x) * ∫ h(x) * -2x dx

w(x) = e-2x * -2∫ e-2x *x dx

w(x) = e-2x * -2(x*e-2x / 2 – e-2x / 4 + C )

w(x) = e-2x * (- x*e-2x + e-2x / 2 + C )

w(x) = [e-4x((1/2) – x] + Ce-2x )

given that

w(x) = y-2

1/y2 = [e-4x((1/2) – x] + Ce-2x )

Hence, the final solution is in the form :

y = 1/√ ( [e-4x((1/2) – x] + Ce-2x )

I think the alternative way for solving of the above Bernoulli differential equation can be performed using a smart method (http://www.rohedi.com) a so-called SMT (Stable Modulation Technique). Can anyone use the SMT to simplify the above problem?

on September 16, 2008 at 10:31 pm |davidGoodluck Mr.AF(A)

on September 25, 2008 at 3:29 pm |guestWow keren…..

on October 11, 2008 at 10:14 am |RivkyIn your statement at a moment, mr.Rohedi capable to give alternative solution form of differential equation. How about with the following form mr?

dy/dx + 4*y*x^3 = -2*(x*y)^3,

for the every initial values x0 and y0.

Thanks mr.